Calculus early transcendentals - Anton, Howard; Bivens, Irl C.; Davis, Stephen (John Wiley & Sons, Inc., 2022)
Early Transcendentals Single Variable , 12th Edition offers students a rigorous and intuitive treatment of single variable calculus, including the differentiation and integration of one variable. Using the Rule of Four, the authors present mathematical concepts from verbal, algebraic, visual, and numerical points of view. The book includes numerous exercises, applications, and examples that help readers learn and retain the concepts discussed within, and discusses polynomials, rational functions, exponentials, logarithms, and trigonometric functions early in the text.